Genetic mapping and functional analysis of a classical tassel branch number mutant Tp2 in maize - Li, Juan; Wang, Xi; Wei, Junfeng; Miao, Xinxin; Shang, Xiaoyang; Li, Lin (Frontiers in Plant Science, 2023)
Tassel branch number is a key trait that contributes greatly to grain yield in maize (Zea mays). Here, we phenotypically characterized and identified a pleiotropic dominant mutant, Teopod2 (Tp2), which exhibited severely decreased tassel branch. Meanwhile, the plant height, ear height, ear leaf length and ear leaf width of mutants were significantly different from the wild type plants. Genetic mapping of Tp2 mutant showed that the causal gene was mapped to an interval of approximately 139-kb on Chromosome 10 harboring two genes Zm00001d025786 and zma-miR156h. Transcriptome analysis showed that the relative expression level of zma-miR156h was significantly increased in mutants. Meanwhile, overexpression of zma-miR156h exhibited significantly decreased tassel branch number, a similar phenotype with Tp2 mutant, suggesting that zma-miR156h is the causal gene of Tp2. Furthermore, we identified several potential down-regulated target genes of zma-miR156 in Tp2 mutants, including ZmSBP13. Knockout materials of ZmSBP13 exhibited decreased tassel branch number, which is similar to the phenotype observed in zma-miR156h overexpression plants, suggesting that ZmSBP13 is a target gene of zma-miR156h. Besides, the potential downstream genes of ZmSBP13 were uncovered and showed that it may target multiple proteins to regulate inflorescence structure. Overall, we characterized and cloned Tp2 mutant, and proposed a zma-miR156h-ZmSBP13 model functioning in regulating tassel branch development in maize.